GAMIFICATION AND TECHNOLOGY IN SCIENCE TEACHING: ENGAGEMENT STRATEGIES IN THE 4TH YEAR OF ELEMENTARY SCHOOL - Mota, Karim Gonçalves da Cunha; Napoleão, Diovana Aparecida dos Santos (Seven Editora, 2025)
This article describes an experience of applying gamification using the Kahoot, Wordwall, and Google Form platforms. For this study, gamification emerged as a promising strategy to engage students in a fun and interesting learning environment, encouraging reflective decision-making processes. It enabled the integration of technology in the teaching of Science in the 4th year of elementary school. Gamification activities were implemented in collaboration with elementary school teachers from a public school, leading to greater student engagement in the classroom. A study was developed that analyzed the platforms by integrating playful elements and quiz design into the students’ learning process, reinforcing the need for adaptation and innovation in education. The results indicated significant improvements in student learning outcomes, reflected in active participation and improvements in assessments. The technology integrated into the Science discipline of the 4th year of elementary school, enabled the integration of students through strategies of creativity and dynamism to solve the situations experienced in everyday life. DOI: https://doi.org/10.56238/sevened2025.018-047